PENGEMBANGAN E-MODUL PEMBELAJARAN IPA SMP UNTUK MENINGKATKAN KPS DASAR - rudi susilo; Eli Trisnowati; Rina Rahayu (Universitas Tidar, 2021)
This study aims to produce e-modules for learning natural sciences for junior high schools to improve basic science process skills, determine the feasibility of e-modules, student responses to e-modules, and the effectiveness of the developed e-modules. This type of research is research and development that uses ADDIE development procedures (analysis, design, development, implementation, and evaluations). The number of research subjects was 22 students in class IX B, 20 students in class VIII B and 19 students in class VIII A. Data analysis used qualitative and quantitative descriptive methods. The types of instruments used are e-module validation sheets, question validation sheets, student questionnaires, and pretest and posttest questions. The results of the e-module development are based on the evaluation of the quality of the e-module by media & material experts, which is 0.89 with a valid category. Student responses to e-modules are categorized as very positive with a percentage of 92.71%. The effectiveness of the e-module is categorized as moderate with an N-gain value of 0.49. The conclusion of this study is that the e-module of natural science learning in junior high school to improve basic science process skills is effectively used in learning.